lntensif Rehabilitasi Kardiak(IREKAF) - Ghazali, Ziyadi (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
Intensive cardiac rehabilitation is the best practice for al cardiac patient and it's shown can increased the quality of life after patients ongoing cardiac surgery. This quasiexperimental study was clone to evaluate the quality of Ufe of cardiac surgery patMint after following the Intensive cardiac rehabllllallon. In this pilot study a total of 30 patients with cardiac problem was admitted to Coronary Intensive Care Unit (CICU). HUSM for cardiac surgery were selected using purpoetve sampling. Patient were divided into two group. Group A (Control group) ,_-a follo JJed Intensive cardiac rehabilitation (ICR) module A(HUSM) and group B (Study IJ'Ol.!P) ,_-a follosJed ICR module B (IREKAF). Quality of life <QOI..) ma asuniments by self administered, using the generic SF 36 . Instrument SF 36 _. used for four times (pre-test , phase 1, phase 2 and phase 3). The repeated measure AHOVA ,_-a used to analyses the dift'el8nt score of QOl among group A and B and the time effect of QOl when patient ~ ICR. The result shown the score QOI. of SF 36 for group B have higher means score p<0.05 compared to group A The time effect for SF 36 shows that there Is only one pair (t1 ~to) for_ which there W88no1i911i~ di~81aoe with~ .~.0.05. The . differences for an the olher pan are slgnllk:a;tt with p-value < alpha 0.08. l"lndlng shows the score is higher for group B compara to grotJp A for SF 36. In generally based on the result we concluded that , the ICR module B is better module to improve the QOl pailents after cardiac surgery. Thia study suggested ihe ·eftective time to evaluate quality of life after 12 weeks of cadiac rehabilitation.